Perfil proteico de la saliva total de pacientes edéntulos parcial y total - Juárez, Rolando Pablo (2022)
Objective. Aim of this study was to characterize the protein profile of whole saliva in partial and complete edentulous and determine the changes in salivary protein expression of adults with varying degrees of tooth loss. Methods. In this observational study, unstimulated saliva samples were collected from 80 adults (age 18-73 years), 20 dentulous and 60 edentulous. Partial and complete edentulous patients (EP) were divided into three groups with different number of teeth lost. Concentration and electrophoretic profile (cellulose acetate membrane and polyacrylamide gels) of the salivary proteins were compared between the groups. Results. Total protein and albumin concentration was highest in the group of dentulous patients (DP) and significantly different in PE groups (p<0.0001). A significant difference (p<0.011) was observed in the gamma globulin fraction between PD versus PE and in the electrophoretic profile of salivary proteins between the different groups. A high number of 66 kDa bands was founded in all groups (p=0.049). Conclusions. The concentration and electrophoretic profile of the salivary proteins of DP and EP were different.